Social participation for the democratization of democracy - Frateschi, Yara (DoisPontos, 2016)
This text aims to analyze the democratic potential of institutionalized social participation. I argue that the expansion of the channels of participation is a tool for deepening democracy to the extent that it favors the empowerment of minorities and of actors systematically alienated from decision-making processes, for it contributes so that they have a chance to interfere in the political agenda and in the formulation of public policies. For this analysis, I will draw on the experience of Brazilian National Conferences and on some aspects of the theory of deliberative democracy developed by Seyla Benhabib regarding the theme of public participation and political judgment.